Assessing the Quality of the HILDA Survey Wave 1 Data - Wooden, M; Watson, N (Melbourne Institute of Applied Economic and Social Research, 2002)
The quality of data generated by any survey is a function of three main elements. These are: (i) the representativeness of the sample; (ii) the completeness of responses (i.e., the extent to which there is missing data, or item-non-response); and (iii) the accuracy of the data (which in turn is a function of the questionnaire design, the accuracy of the responses provided, and the accuracy with which responses are recorded, coded and entered into the database). In addition, for the HILDA Survey, added concerns arise as a result of the need to match data, both across individuals within the same households and within individuals. This is a consequence of both the presence of multiple instruments and the desire to construct household-level variables. This paper provides an assessment of the data obtained for the first wave of the HILDA Survey (conducted in 2001) against each of these criteria.
HILDA Project Technical Paper Series
HILDA Project Technical Paper Series
Keywords: Surveys and Survey Methodology -- Dataset cleaning and development; Surveys and Survey Methodology -- Questionnaire development; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Dataset cleaning and development; Questionnaire development; Surveys and Survey Methodology